Mesenchymal Stromal Cells as a Cellular Target in Myeloid Malignancy: Chances and Challenges in the Genome Editing of Stromal Alterations - Banjanin, Bella; Schneider, Rebekka K. (Frontiers in Genome Editing, 2021)
The contribution of bone marrow stromal cells to the pathogenesis and therapy response of myeloid malignancies has gained significant attention over the last decade. Evidence suggests that the bone marrow stroma should not be neglected in the design of novel, targeted-therapies. In terms of gene-editing, the focus of gene therapies has mainly been on correcting mutations in hematopoietic cells. Here, we outline why alterations in the stroma should also be taken into consideration in the design of novel therapeutic strategies but also outline the challenges in specifically targeting mesenchymal stromal cells in myeloid malignancies caused by somatic and germline mutations.